1996
DOI: 10.1182/blood.v87.10.4072.bloodjournal87104072
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of interferon in treating chronic hepatitis C in children with a history of acute leukemia

Abstract: Interferon (IFN) is effective in treating adults as well as children with chronic hepatitis C. We investigated the efficacy of IFN therapy in 13 children with underlying acute leukemia who had chronic hepatitis C (age range, 5 to 17 years; mean age, 9.9 years). Natural IFN- alpha was administered at a dose of 0.1 mega unit (MU)/kg (maximum dose, 6.0 MU) daily for 2 weeks and then three times per week for an additional 22 weeks (total dose, 8 MU/kg). IFN treatment was initiated at least 2 years after the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In our previous study, which evaluated conventional IFN treatment efficacy for children with transfusion-acquired CHC, most of the genotypes were genotype 1. 13 Therefore, a higher rate of genotype 2 in children may be a feature of mother-to-child transmission in Japan. Second, this study adopted a relatively higher dose of PEG IFN-a-2a, and the increase in dose was based on viral response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, which evaluated conventional IFN treatment efficacy for children with transfusion-acquired CHC, most of the genotypes were genotype 1. 13 Therefore, a higher rate of genotype 2 in children may be a feature of mother-to-child transmission in Japan. Second, this study adopted a relatively higher dose of PEG IFN-a-2a, and the increase in dose was based on viral response.…”
Section: Discussionmentioning
confidence: 99%
“…F ROM MARCH 2005 to April 2011, 31 children (19 boys, 12 girls; median age, 6 years; range, [3][4][5][6][7][8][9][10][11][12][13][14] were treated with PEG IFN-a-2a monotherapy at our single center. They were all infected through mother-tochild transmission and were all treatment naive.…”
Section: Patientsmentioning
confidence: 99%
“…Conventional IFN monotherapy in children gives an SVR rate of 33-45% (26% in genotype 1, 70% in other genotypes), which is much better than the rate of 19% observed in adults. [23][24][25] The better response rate in children may be the result of the short time between HCV infection and treatment, the relatively higher dose of IFN and lack of comorbid diseases. 10,26 An SVR rate of approximately 30% is obtained with PEG IFN monotherapy in adults.…”
Section: Discussionmentioning
confidence: 99%
“…10 Three of eight patients with genotype 1 achieved SVR, and this rate was not so high compared to conventional IFN monotherapy for 6 months, as we previously described (43% vs 40%). 25 A recently published abstract from the Peds-C trial showed an SVR rate with PEG IFN monotherapy of only 21%. 27 Therefore, SVR rates in children show little or no difference between conventional IFN monotherapy and PEG IFN monotherapy, whereas a significant difference is observed in adult cases.…”
Section: Discussionmentioning
confidence: 99%
“…43 Even though the studies included several types of patients, and different dosages, schedules and types of interferon were used, the sustained virological response rates, when reported, were remarkably similar among the studies, ranging from 33% to 45%. 29,[44][45][46][47][48][49][50][51] These sustained virological response rates are significantly higher than those reported in large trials of interferon monotherapy in adult patients. A systematic analysis of these heterogeneous studies was recently reported.…”
Section: Treatment Of Hcv Infection In Childrenmentioning
confidence: 99%